2005
DOI: 10.1093/protein/gzi021
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fc–erythropoietin structure and pharmacokinetics by modification at a disulfide bond

Abstract: Erythropoietin (Epo) is a cytokine that controls the production of red blood cells (RBCs). Epo acts continuously on RBC precursors to prevent apoptosis, so it is important to maintain high levels of Epo activity when treating anemic patients. We describe here modified human Epo [Epo(NDS)] with mutations His32Gly, Cys33Pro, Trp88Cys and Pro90Ala that result in the rearrangement of the disulfide bonding pattern from Cys29-Cys33 to Cys29-Cys88 and that, in the context of an Fc-Epo(NDS) fusion protein, lead to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Binding of 10F7-EPO R150A to huGYPA reduces its maximal plasma concentration (C max ) and increases its terminal plasma half-life. EPO pharmacokinetics can be influenced by receptor binding, glycosylation, and molecular weight, which affect clearance through receptor-mediated endocytosis by EPO-Rs, liver asialoglycoprotein receptors, and kidney filtration, respectively (13,29,34). Moreover, binding to huGYPA on mature RBCs is expected to create a sink effect (35), through which most of 10F7-EPO R150A should equilibrate with the free plasma state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of 10F7-EPO R150A to huGYPA reduces its maximal plasma concentration (C max ) and increases its terminal plasma half-life. EPO pharmacokinetics can be influenced by receptor binding, glycosylation, and molecular weight, which affect clearance through receptor-mediated endocytosis by EPO-Rs, liver asialoglycoprotein receptors, and kidney filtration, respectively (13,29,34). Moreover, binding to huGYPA on mature RBCs is expected to create a sink effect (35), through which most of 10F7-EPO R150A should equilibrate with the free plasma state.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons between treatments were done using Student's t test. *P < 0.1; ***P < 0.005. and binding to asialoglycoprotein receptors should remove only a subpopulation of drug molecules (29). Finally, clearance of RBCbound drug via splenic apoptosis should be slow (36).…”
Section: Resultsmentioning
confidence: 99%
“…This EPO-GM-CSF complex proved to be able to stimulate erythropoiesis in cynomolgus monkeys (28) but was later found to induce anti-EPO antibodies, causing severe anemia (29). Yet another approach is the genetic fusion of EPO with the Fc region of human IgG (Fc-EPO) (30). This molecular modification promotes recycling out of the cell upon endocytosis via the Fc recycling receptor (31,32), again providing an alternative mechanism for enhancing circulating half-life.…”
Section: Other Protein-based Epo Derivativesmentioning
confidence: 99%
“…This EPO-GM-CSF complex proved to be able to stimulate erythropoiesis in cynomolgus monkeys (Coscarella et al, 1998a), but was later found to induce anti-erythropoietin antibodies, causing severe anemia (Coscarella et al, 1998b). Yet another approach is the genetic fusion of EPO with the Fc region of human immunoglobulin G (Fc-EPO) (Way et al, 2005). This molecular modification promotes recycling out of the cell upon endocytosis via the Fc recycling receptor (Capon et al, 1989;Yeh et al, 1992), again providing an alternative mechanism for enhancing circulating half-life.…”
Section: Potential Strategies For Modifying Erythropoietin To Crementioning
confidence: 99%